Template‐Dependent Photochemical Reactivity of Molecular Metal Oxides. Issue 24 (23rd April 2015) - Tucher, Johannes; Peuntinger, Katrin; Margraf, Johannes T.; Clark, Timothy; Guldi, Dirk M.; Streb, Carsten
Abstract A combined experimental and theoretical study shows that the photooxidative activity of two isostructural metal oxide clusters depends on their internal templates. To this end, two halide‐templated bismuth vanadium oxide clusters [X(Bi(dmso)3)2V12O33]− (X=Cl−, Br−) are reported and fully characterized. The two clusters show similar absorption features and illustrate that bismuth incorporation results in increased visible‐light absorption. Significantly higher photooxidative activity is observed for the bromide‐templated cluster compared with the chloride‐templated one. Detailed photophysical assays and complementary DFT calculations suggest that the more efficient triplet excited state formation in the Br−‐containing cluster is the decisive step in the photocatalysis and is due to the heavy‐atom effect of the bromide. This concept can therefore open new pathways towards the optimization of photocatalytic activity in metal oxide clusters.